Perencanaan Sistem PengelolaanAir Limbah Domestik di Unit Pengembangan (UP) I Rungkut, Kota Surabaya - Albanjari, Muhammad Taufik; Naniek Ratni, Juliardi A. R. (Universitas Bojonegoro, 2023)
Development Unit I Rungkut, Surabaya, faces significant sanitation issues due to domestic waste being directly discharged into drainage channels. To address this, a Wastewater Distribution System and Wastewater Treatment Plant (WWTP) were designed. The system utilizes a shallow sewer type, ideal for densely populated areas with gentle slopes. The WWTP incorporates various technologies, including Bar Screen, Equalization Tank, Flotation Tank, Oil Settlement Tank, Mixing Tank (Coagulation-Sedimentation), Food Chain Reactor, Final Clarifier, and Sludge Drying Beds. The area is divided into 5 service blocks, serving a population of 24,405. The study indicates that the Food Chain Reactor will be the main processing unit. The distribution system uses HDPE pipes with diameters ranging from 355 to 500 mm. The total investment is estimated at Rp. 87,832,528,386, with monthly operation and maintenance costs of Rp. 4,000 per House Connection (SR).